The Role of Response-Shift in Studies Assessing Quality of Life Outcomes Among Cancer Patients: A Systematic Review - Ilie, Gabriela; Bradfield, Jillian; Moodie, Louise; Lawen, Tarek; Ilie, Alzena; Lawen, Zeina; Blackman, Chloe; Gainer, Ryan; Rutledge, Robert D. H. (Frontiers in Oncology, 2019)
Objective: Response-shift has been cited as an important measurement consideration when assessing patient reported quality of life (QoL) outcomes over time among patients with severe chronic conditions. Here we report the results of a systematic review of response shift in studies assessing QoL among cancer patients. Methods: A systematic review using MEDLINE, EMBASE, and PsychINFO along with a manual search of the cited references of the articles selected, was conducted. A quality review was performed using STROBE criteria and reported according to PRISMA guidelines. Results: A systematic review of 1487 records published between 1887 and December 2018 revealed 104 potentially eligible studies, and 35 studies met inclusion criteria for content and quality. The most common cancer patient populations investigated in these studies were breast (18 studies), lung (14 studies), prostate (eight studies) and colorectal (eight studies). Response shift was identified among 34 of the 35 studies reviewed. Effect sizes were reported in 17 studies assessing QoL outcomes among cancer patients; 12 of which had negligible to small effect sizes, four reported medium effect sizes which were related to physical, global QoL, pain and social (role) functioning and one reported a large effect size (fatigue). The most prevalent method for assessing response shift was the then-test, which is prone to recall bias, followed by the pre-test and post-test method. Given the heterogeneity among the characteristics of the samples and designs reviewed, as well as the overall small to negligible effect sizes for the effects reported, conclusions stating that changes due to internal cognitive shifts in perceived QoL should account for changes observed in cancer patients’ QoL outcomes should be interpreted with caution. Conclusion: Further work is needed in this area of research. Future studies should control for patient characteristics, time elapsed between diagnosis and baseline assessment and evaluate their contribution to the presence of response shift. Time between assessments should include short and longer periods between assessments and evaluate whether the presence of response shift holds over time. Possible avenues for inquiry for future investigation are discussed.